Affirming the Historical Vision of Madrasah in the Global Context: Religious, Popular, Centers of Excellence, Core of Learning Society, and Diversity - Mukhibat, Mukhibat (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Madrasah is still interesting to talk over. Madrasah, as an Islamic education institution in Indonesia, has emerged and developed as Islam came to Indonesia. The madrasah has developed into some levels and types as the Indonesia developed. So that madrasah, as an Islamic education, has been a part of national education system. With the emergence of Law Number 20 Year 2003 on the National Education System in Reform era in Indonesia, madrasah exactly equate with public schools. This equalisation creates types of madrasah, such as madrasah âskillâ, madrasah âexcellenceâ, madrasah âmodelâ, and religious madrasah. Until now, madrasah is at the crossroad, pulled between the maintenance of historical tradition and the adopting a new developing phase. Madrasah is supposed to be built on the foundation of Islamic values, the essential characters of Islamic education history, and the formula of futureâs challenge. The Islamic characters and the popularity of madrasah is the identity of history reflected on its education curriculum. Madrasah is obliged to apply the bottom vision and mission of âpesantrenâ (Islamic boarding school), namely âtafaqquh fi al-dinâ (fully understanding on religious affairs), by increasing society participation in the empowerment of madrasah by implementing accountable management and quality oriented, which will encourage madrasah to be centers of excellence; and increasing participation, so that madrasah will be the core of learning society, capable, and integrated with society.KEY WORDS: Madrasah, globalization, vision, accountable management, and quality oriented.About the Author: Dr. Mukhibat is a Lecturer of Islamic Education Management at the Department of Tarbiyah (Education) in STAIN (Sekolah Tinggi Agama Islam Negeri or State Islamic Religious College) Ponorogo, Jalan Pramuka No.156 Ponorogo, East Java, Indonesia. Corresponding author is: mukhibat@yahoo.co.idHow to cite this article? Mukhibat. (2016). âAffirming the Historical Vision of Madrasah in the Global Context: Â Religious, Popular, Centers of Excellence, Core of Learning Society, and Diversityâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.263-274. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (November 27, 2015); Revised (January 20, 2016); and Published (April 28, 2016).